MaRIS - Migration and Refugee Information Studies Research Project - Eskola, Eeva-Liisa; Hämäläinen, Riitta; Ojanperä, Anne; Ruokolainen, Hilda (Informaatiotutkimus, 2017)
According to the statistics of the United Nations High Commissioner for Refugees (UNHCR 2017) from 2015 there were 65.3 million forcibly displaced people around the world. Global migration can be expected to be a large question in the world also in the future, for example, the recent refugee and asylum seekers crises in Europe brought with it a number of challenges on many levels. One of the major challenges is connected to communication and information. The goal of the MaRIS project is to strengthen the research in the area of refugee information practices, needs, seeking and use, as well as to promote dialogue and collaboration between the researchers and the practitioners interested in the topic.